2016
DOI: 10.1016/j.jfineco.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity aversion and household portfolio choice puzzles: Empirical evidence

Abstract: We test the relation between ambiguity aversion and five household portfolio choice puzzles: nonparticipation in equities, low allocations to equity, home-bias, own-company stock ownership, and portfolio under-diversification. In a representative US household survey, we measure ambiguity preferences using custom-designed questions based on Ellsberg urns. As theory predicts, ambiguity aversion is negatively associated with stock market participation, the fraction of financial assets in stocks, and foreign stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
153
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(172 citation statements)
references
References 75 publications
(104 reference statements)
15
153
2
2
Order By: Relevance
“…[47] (3) "Out of 10 women who test positive as you did, only 1 has breast cancer." [20] (4) The chance that you have breast cancer is about 1%."…”
Section: Frequency Versus Probability Format and The Ktando Programmentioning
confidence: 99%
“…[47] (3) "Out of 10 women who test positive as you did, only 1 has breast cancer." [20] (4) The chance that you have breast cancer is about 1%."…”
Section: Frequency Versus Probability Format and The Ktando Programmentioning
confidence: 99%
“…Jappelli and Padula (2014) found that financial literacy has positive correlation with investors' wealth and portfolio diversification and suggested that financial literacy allows investor better investment opportunities. Dimmock, Kouwenberg, Mitchell, and Peijnenburg (2016) pointed out that financial literacy improves the financial decisions of investor and reduces the ambiguity aversion. Bachmann and Hens (2015) elucidated that investors who rely on professionals' advice and consult with others, have higher investment because they consistently learn from financial advisors.…”
Section: Literature Review Financial Literacy and Portfolio Diversifimentioning
confidence: 99%
“…Other empirical studies mainly focus on portfolio choice problems. For instance, Dimmock et al (2016) investigated market participation of households under ambiguity. They found that investors under-diversified their portfolios due to ambiguous information and the 2008 financial crisis could be contributed to ambiguity aversion.…”
Section: Introductionmentioning
confidence: 99%